2014
DOI: 10.1007/s00436-014-4048-9
|View full text |Cite
|
Sign up to set email alerts
|

Three Unicapsula species (Myxosporea: Trilosporidae) of Asian marine fishes, including the description of Unicapsula setoensis n. sp. in the yellowfin goby (Acanthogobius flavimanus) from the Inland Sea of Japan

Abstract: The myxosporean genus Unicapsula (Multivalvulida: Trilosporidae) is defined as having a spore with three unequal shell valves and polar capsules, of which one is prominent and the two other polar capsules are rudimentary. Genetic characterization of members of the genus, currently 11 nominal species, is, at present, unsatisfactory yet when comparing to the closely related genus Kudoa (Multivalvulida: Kudoidae). In the present study, we characterized long ribosomal RNA gene (rDNA) sequences of three Unicapsula … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…Morphological data obtained from this study showed that U. fatimae was morphologically comparable to what is termed as the “sub-spherical” Unicapsula species that include Unicapsula andersenae Miller and Adlard 2013 , Unicapsula seriolae Lester 1982 , Unicapsula pflughfelderi Schubert et al 1975 , Unicapsula galeata Naidjenova and Zaika 1970 , Unicapsula shulmani Aseeva and Krasin 2001 , Unicapsula pacifica Aseeva and Krasin 2001 , Unicapsula setoensis Tomochi et al 2014 , and Unicapsula chirocentrusi Sarkar 1984 , and was morphologically distinct from all other Unicapsula species. U. andersenae from (Argyrosomus japonicus) Temminck and Schlegel 1843 , (Acanthopagrus australis) Günther 1859; ( Eleutheronema tetradactylum) Shaw, 1804; (Lutjanus russellii) Bleeker 1849 and (Sillago ciliata) Cuvier 1829 from Australia was genetically the most closely related species to U. fatimae in the BLAST search with approximately 97 % similarity.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Morphological data obtained from this study showed that U. fatimae was morphologically comparable to what is termed as the “sub-spherical” Unicapsula species that include Unicapsula andersenae Miller and Adlard 2013 , Unicapsula seriolae Lester 1982 , Unicapsula pflughfelderi Schubert et al 1975 , Unicapsula galeata Naidjenova and Zaika 1970 , Unicapsula shulmani Aseeva and Krasin 2001 , Unicapsula pacifica Aseeva and Krasin 2001 , Unicapsula setoensis Tomochi et al 2014 , and Unicapsula chirocentrusi Sarkar 1984 , and was morphologically distinct from all other Unicapsula species. U. andersenae from (Argyrosomus japonicus) Temminck and Schlegel 1843 , (Acanthopagrus australis) Günther 1859; ( Eleutheronema tetradactylum) Shaw, 1804; (Lutjanus russellii) Bleeker 1849 and (Sillago ciliata) Cuvier 1829 from Australia was genetically the most closely related species to U. fatimae in the BLAST search with approximately 97 % similarity.…”
Section: Resultsmentioning
confidence: 57%
“…Unicapsula species are unique among other Trilosporidae because only one of the three polar capsules is fully developed and functional, whereas the remaining two are rudimentary and barely visible (Alama-Berjamo et al 2009 ; Miller and Adlard 2013 ). Since the description of the genus and the type species in 1924 by Davis, a total of 12 species of Unicapsula have been recorded from different localities and a wide range of marine host species (Naidjenova and Zaika 1970 ; Schubert et al 1975 ; Sarkar 1984 ; Sarkar 1999 ; Diebakate et al 1999 ; Miller and Adlard 2013 ; Tomochi et al 2014 ). Similar to their closely related group, the Kudoidae, some members of Unicapsula have been associated with negative impact on their hosts mostly associated with esthetic issues involving macroscopic pseudocysts or myoliquefaction (Lester 1982 ; Alama-Berjamo et al 2009 ; Miller and Adlard 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Davis (1924) referred to infected fish as ‘wormy halibut’, referring to their heavy parasite load. The second species to be described, Unicapsula galeata Naidjenova et Zaika, 1970, was discovered in the trunk muscle of the whitesaddle goatfish Parupeneus ciliates (Lacepède, 1802) more than 40 years later after the erection of the genus (Naidjenova and Zaika, 1970), and a total of only 13 species have been described to date (Schubert et al ., 1975; Alama-Bermejo et al ., 2009; Miller and Adlard, 2013; Tomochi et al ., 2014; Yokoyama et al ., 2014; Al-Jufaili et al ., 2016). As partially reflected in a limited number (only 13) of the currently recognized Unicapsula spp., Miller and Adlard (2013) suspected that the richness of Unicapsula spp.…”
Section: Introductionmentioning
confidence: 99%
“…), которые паразитируют в груперах и баррамунди [19]. Первые исследования многостворчатых миксоспоридий Восточного моря с привлечением методов молекулярной генетики охватили изучение Unicapsula pyramidata в Nemipterus japonicus [18], Kudoa monodactyli из Monodactylus argenteus [14] и Kudoa scomberomori из Scomberomorus guttatus [15]. Рыб обследовали методом неполного паразитологического вскрытия [2].…”
unclassified